Corporate governance, sustainability initiatives and firm performance: theoretical and conceptual perspectives - Adedeji, Babatunji Samuel (AESS Publications, 2019)
The objective of this paper is to generate a discuss as to the degree to which corporate governance and sustainability initiatives are predictor variables for firm performance, with the premise that firms have to be deliberately placed for them to harness the prospects available in their immediate environments. In relation to this study, the stakeholders, agency and institutional theories form the bedrock for the underpinning theories used for formulating the research framework with respect to the relationships among firm performance, corporate governance and sustainability initiatives respectfully. Less research efforts are involved in this area of study in the less developed nations, particularly with respect to the impacts of corporate governance on the environmental and social initiatives as well the financial and non-financial corporate performances of firms. Therefore, scholars and practitioners are encouraged to advance the body of knowledge in this study area for the global enhancement of productivity, as the review has conceptualised the integration of corporate governance and sustainability initiatives as strategic tools for enhancing firm performances locally and internationally.